Unlocking The Bioactivity Potential: Molecular Insights and Predictions of Salen, Salophen, Allicin, Curcumin, and Piperine - Anamika Pandey; Udita Singh; Mandakini Gupta; Sumit Chaudhary; Ranjeet Kumar; Piyush Kumar Sonkar (International Journal of Cheminformatics, 2024)
In this work, the prediction of the biological activity of several significant molecules, including salen, salophen, allicin, curcumin, and piperine, are discussed. Using Molinspiration software, the molecular properties of these compounds were calculated. These molecules are highly significant due to their extensive potential in medical applications. Salen and salophen, for instance, play crucial roles in cancer chemotherapy and act as inhibitors of angiogenesis. Curcumin is renowned for its antioxidant properties, piperine is recognized as an alkaloid and anti-arthritic agent, and allicin is a phytochemical known for its anti-cancer effects. Biological pharmacological activity refers to the beneficial impacts a drug or molecule has on living organisms. The bioactivity of these molecules was predicted using Mo inspiration, which provides cheminformatics tools for molecular interpretation and processing. This software facilitates the conversion of SMILES and SD files, normalization of molecules, and the calculation of various molecular properties. Consequently, it significantly aids in predicting the bioactivity of these crucial molecules, which can lead to advancements in their medical applications. By understanding their molecular properties and potential biological activities, researchers can better harness these molecules for therapeutic uses, ultimately contributing to improved health outcomes.
Keywords: Allicin; Molinspiration; Piperine; Salen; Salophen; curcumin